Revisiting the challenge of intentional value shift: reply to Ives and Fischer. Issue 6 (9th October 2017) - Manfredo, Michael J.; Bruskotter, Jeremy T.; Teel, Tara L.; Fulton, David C.; Oishi, Shigehiro; Uskul, Ayse K.; Redford, Kent H.; Schwartz, Shalom H.; Arlinghaus, Robert; Kitayama, Shinobu; Sullivan, Leeann
Abstract : Article impact statement : Conservation values are unlikely to change through intentional efforts.